Genetic characterization of Philippine Saba germplasm collection using microsatellite markers - dela Cruz, Fides Marie R.; Mendoza, Evelyn Mae T.; Garcia, Roberta N.; Huelgas, Visitacion C.; Gueco, Lavernee S.; Sandoval, Carlo Miguel C.; Laude, Rita P. (2020)
The genetic diversity among 75 Philippine Saba gene bank collections and four non-Saba accessions were analyzed using microsatellite markers or simple sequence repeats (SSRs). Eleven primer pairs were found to be polymorphic across all genotypes and amplified a total of 28 alleles. The discriminatory power of the primers was moderately high with mean polymorphism information content (PIC) value of 0.38. Genetic diversity was measured in terms of heterozygosity, fixation index, and genetic distance. Average gene diversity or expected heterozygosities ranged from 0.09?0.58, with an average of 0.48. Observed heterozygosities ranged from 0.09?0.95, with a mean of 0.80. Fixation indices (mean = ?0.61) were negative, which suggests an excess of heterozygotes and shows that diversity has been maintained within the gene bank collection. Cluster analysis revealed that the greatest genetic distance (GD = 0.69) was observed between Lakatan (AAA) and Cardaba 6 (ABB/BBB) bananas. Therefore, the SSR markers used were able to separate the Saba cultivars from the non-Saba cultivars. Furthermore, the markers were able to separate the seedy diploid cultivar Pacol from the rest of the triploid Saba cultivars. Future studies can survey other potential SSRs for better discrimination among Saba samples. (Author's abstract)